Dayuma, life under Waorani spears: a tragedy that shocked the world, a vision that refused to die - Wallis, Ethel Emily (YWAM Publishing, 1996)
Jim Elliot, Nate Saint, Pete Fleming, Roger Youderian, and Ed McCully chose to lay down their lives on a sandy beach in Ecuador. Their lives and sacrifice come full circle in the true story of Dayuma. Violent, unexpected death was a way of life for the Waorani tribe living deep in the Ecuadorian jungle. When her father is brutally speared, young Dayuma is faced with a choice: flee to the outside world to those thought to be cannibals or stay in the jungle to face certain death from the spears of the tribal killers